Emergent balloon pulmonary angioplasty in a patient with central‐type chronic thromboembolic pulmonary hypertension with cardiac shock. Issue 12 (13th December 2022) - Tamura, Hiroto; Hosokawa, Shinobu; Yuba, Kenichiro
Abstract: The standard treatment of chronic thromboembolic pulmonary hypertension (CTEPH) is pulmonary endarterectomy (PEA); however, it may be unsuitable in the presence of comorbidities such as cardiac shock and severe hypoxia. We describe a successful case of emergent balloon pulmonary angioplasty performed before PEA in a patient with deteriorating central‐type CTEPH. Abstract : An emergent balloon pulmonary angioplasty could be an alternative option before conventional pulmonary endarterectomy in a patient with deteriorating central‐type chronic thromboembolic pulmonary hypertension.